Bolhas finas geradas por novo sistema de vazão pulsada de gás e o seu papel em processos de transferência de massa - Pereira, Rauber Daniel (2023)
The use of small-sized bubbles, known as fine bubbles or microbubbles, in mass transfer operations has been extensively discussed, and various bubble generation methods have been developed and applied. However, methods involving the generation of small-sized bubbles at pilot or industrial scale remain unexplored, as well as the role these bubbles play in mass transfer operations. This study aimed to develop a new system for generating fine bubbles, referred to as the Fine Bubble Generator (FBG), within a bubble column reactor. This system comprises a high-frequency (>70 Hz) solenoid valve for generating pulsed gas flow and machined spargers with conventional perforations, i.e., perforations that can be commercially produced (orifices diameters above 0.3 mm). The system was developed and characterized in a pilot-scale bubble column reactor (173 L) by determining the bubble diameters generated under different operational conditions of gas flow, operational frequency, and liquid medium composition. An optimal operating region was observed in the range of 100 to 150 Hz in non-coalescent media, where reductions in bubble diameter of around 33% compared to conventional aeration were achieved. Subsequently, the system was applied to a 10.0 L bubble column reactor to evaluate the volumetric oxygen transfer coefficient (kLa) in coalescent and non-coalescent liquid media. In those operations, spargers with conventional perforations (R8H) and sintered-type spargers (SSD), which naturally generate microbubbles (db < 1000 μm), were used. The pulsed flow system combined with the R8H sparger led to increases in kLa values of approximately 50% and 80% compared to conventional aeration (continuous flow), for non-coalescent and coalescent media, respectively. However, for the SSD sparger, no significant change in kLa was observed, supporting the hypothesis of a minimum natural frequency of bubble formation that needs to be surpassed for premature detachment to occur. Furthermore, the FBG system was employed in ethanol stripping operations within 10.0 L bubble column reactors (using both R8H and SSD spargers) and a 50.0 L bubble column reactor (using a PS3 sparger - conventional perforations of 0.3 mm, scaled in number of orifices for a 50.0 L volume). At this stage of the study, bubble saturation was confirmed under various operational conditions of gas flow rate and bubble diameter. A mathematical model was developed to quantify the fraction of ethanol removed through thermodynamic-driven entrainment (or vaporization) and mechanical entrainment. The latter was found to enrich the gas phase with ethanol concentrations surpassing those achieved through thermodynamic equilibrium selectivity, reaching up to 15 times the liquid phase concentration. This demonstrates the complexity of mechanical entrainment, which depends on bubble diameter, in operations involving the removal of volatile solvents. It also illustrates that, under the right operational conditions, this phenomenon can enhance the efficiency of the stripping process. The final phase of the study involved applying the FBG system to extractive alcoholic fermentation in 10.0 L and 50.0 L bubble column reactors, achieving a productivity increase of around 15% compared to conventional batch fermentation using a specific CO2 flow rate of 0.4 vvm.